2017
DOI: 10.1002/pbc.26692
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag use in a patient with Wiskott–Aldrich syndrome

Abstract: Wiskott-Aldrich syndrome (WAS) is an inherited X-linked disorder characterized by microthrombocytopenia, immunodeficiency, and eczema. Hematopoietic stem cell transplantation (HSCT) is the treatment of choice. Eltrombopag, a thrombopoietin receptor agonist, may be useful to prevent bleeding while awaiting HSCT. We present a case of a male with WAS, profound thrombocytopenia, and bleeding diathesis successfully managed with eltrombopag before HSCT. Eltrombopag was given for 32 weeks obtaining a stable platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“… 144 Thrombopoietin-mimetics have more recently been used for a patient with a DIAPH1 mutation prior to hip arthroplasty and as a “bridge” for a child with WAS and severe thrombocytopenia awaiting HSC transplantation. 145 , 146 The goal in such situations is to transiently increase the platelet count to >50×10 9 platelets/L. Romiplostim has been successful in correcting the platelet count resulting from mutations in THPO in congenital amegakaryocytic thrombocytopenia in which the patient’s own thrombopoietin is absent or non-functional.…”
Section: Treatmentmentioning
confidence: 99%
“… 144 Thrombopoietin-mimetics have more recently been used for a patient with a DIAPH1 mutation prior to hip arthroplasty and as a “bridge” for a child with WAS and severe thrombocytopenia awaiting HSC transplantation. 145 , 146 The goal in such situations is to transiently increase the platelet count to >50×10 9 platelets/L. Romiplostim has been successful in correcting the platelet count resulting from mutations in THPO in congenital amegakaryocytic thrombocytopenia in which the patient’s own thrombopoietin is absent or non-functional.…”
Section: Treatmentmentioning
confidence: 99%
“…• Clinical study with eltrombopag (n = 8): after 22-209 weeks of treatment, spontaneous bleeding was reduced in 75% of patients [34] • Case study with eltrombopag: one patient achieved a stable platelet count and remission of bleeding symptoms [35] • Clinical trial with eltrombopag ongoing [42] Although there is no evidence of an increased risk of lymphoid malignancies with TPO-RAs, careful monitoring is recommended Potential effects of long-term eltrombopag exposure on the success rate of transplant engraftment after HSCT have not been studied…”
Section: Risk Of Hematological Malignancymentioning
confidence: 99%
“…Among the three patients who did not meet the response criteria, one continued eltrombopag because of a small reduction in bleeding symptoms combined with the lack of a better alternative, and two patients discontinued: one of them switched to romiplostim and experienced an increase in the platelet count (> 20 × 10 9 L –1 ) and decreased bleeding . A recent case study reported that another patient with WAS, who had severe thrombocytopenia and bleeding, was treated with eltrombopag and achieved a stable increase in the platelet count and remission of bleeding symptoms .…”
Section: Tpo‐rasmentioning
confidence: 99%
“…Recently, new thrombopoietin agonists, such as romiplostim (Nplate; Amgen, Thousand Oaks, CA, USA) and eltrombopag (Revolade; GlaxoSmithKline, Brentford, UK), have been used to treat thrombocytopenia to prevent life‐threatening bleeding while patients wait for HSCT . In particular, eltrombopag has been tested in a clinical trial (NCT00909363) in patients with WAS and XLT that reported an increase in PLT counts in the majority of patients …”
Section: Wasmentioning
confidence: 99%
“…66 In particular, eltrombopag has been tested in a clinical trial (NCT00909363) in patients with WAS and XLT that reported an increase in PLT counts in the majority of patients. 70,71 The gold standard of treatment is HSCT, 72 however, this treatment is available only in a minority of patients. In general, PLT counts increase after transplantation, both in patients who underwent splenectomy and those who did not, and is dependent on the degree of myeloid chimerism.…”
Section: Current Therapiesmentioning
confidence: 99%